Masyarakat Bebas Vektor dan Binatang Pembawa Penyakit dengan Konsep Pemberdayaan Ibu PKK - Dewi, Mirnawati; Krestina, Widya; Wanto, Wahyu Anggar (Universitas Dinamika, 2025)
This is a new author guidelines and article template of Manhaj: Jurnal Penelitian Vectors are insects, rodents, birds, or other animals that can carry disease pathogens. The most common vectors are blood-sucking insects, such as mosquitoes and ticks. Vector-borne diseases occur in animals and humans. However, animals can sometimes carry harmful germs that can spread to humans and cause diseases – these are known as zoonotic diseases. Zoonotic diseases are caused by harmful germs such as viruses, bacteria, parasites, and fungi. This service aims to increase public knowledge about vector bioecology and disease-carrying animals so that the community can carry out appropriate control independently. The activity method is in the form of material delivery, answers, and tests. The results of the pre-test showed that 75% of participants did not understand that what was a vector and 50% of participants did not know the type of vector. 56.25% of participants did not know that rats played the role of disease carriers. The results of the post test showed that 100% of the participants knew about the vector and the animal that carried the disease.